Privatization in Mexico - Alberto Chong; Florencio Lopez-de-Silanes (Inter-American Development Bank, Research Department, 2004)
Over the last 20 years, Mexico redefined the role of the state in its economy through an ambitious program to liberalize trade, promote efficiency and reduce the size and scope of the state-owned sector. In Mexico, privatization led to a significant improvement in firm performance, as profitability increased 24 percentage points and converged to levels similar to those of private firms. From this increase, at most 5 percent can be attributed to higher prices and 31 percent to transfers from workers, with the remaining 64 percent representing productivity gains. There is evidence that privatization provides other social benefits, as greater access to services, which usually follows privatization, leads to welfare gains for the poorest consumers that outweigh any increase in prices. Moreover, an often-overlooked aspect of privatization is its fiscal impact, whereby the proceeds from the sale are augmented by reduced subsidies and increased taxes and can help pay off debt or finance social spending. The Mexican privatization program can provide a valuable guide to privatization dos and donts: First, the privatization process must be carefully designed and run in a transparent way. Special requirements such as bans on foreign direct investment or cash-only payments lead to substantial price discounts for firms sold, while simplicity breeds competition and leads to higher prices. A transparent program can also help quell the tendency of politicians to favor their friends by tweaking the rules of the game. Second, restructuring firms prior to privatization is counterproductive in raising net sale prices and should be avoided. Governments spend substantial resources on politically motivated investment or efficiency programs that are not valued by bidders and which can rarely be justified on the social ground on which they are sold. Additionally, restructuring programs lengthen the privatization process considerably and lower prices for firms sold in the case of Mexico, each month of delay reduced the sale price by 2. 2 percent. Finally, this paper argues that it is essential to carefully deregulate and re-regulate privatized firms to ensure that they behave appropriately as well as to provide a corporate governance framework to ensure firms are able to finance their operations without relying on the Government for help.
Keywords: 330; Privatisierung; Unternehmenserfolg; Mexiko